Cultura capitalista e crise ambiental: o despertar social quanto à necessidade das leis ambientais = Capitalist culture and environmental crisis: the social awakening as to the necessity of environmental laws - Kruse, Bárbara Cristina (2015)
Submitted by Lâmoni null (lamoni@stj.jus.br) on 2015-11-24T17:38:19Z No. of bitstreams: 1 cultura_capitalista_crise_kruse.pdf: 630624 bytes, checksum: 3c95c30c3fe96af69c1beb082efc6e38 (MD5)